Kondisi Fisika Kimia Air Sungai Yang Bermuara di Teluk Sawaibu Kabupaten Manokwari - Muhammad Irwan; Alianto Alianto; Yori Turu Toja (Jurnal Sumberdaya Akuatik Indopasifik, 2017)
This research was conducted in three small rivers (Momo, Sahara and Konto), which empties into the Gulf Sawaibu Manokwari District. Water sampling for the third observation station made for the measurement of physical parameters such as temperature, TDS, TSS and turbidity, and chemical parameters pH, DO, COD, BOD, nitrate (NO3), phosphate (PO4) and Ammonia. The purpose of this study was to determine the physical quality of the river water chemistry research sites, and compared with water quality standards based on Government Regulation No. 82 of 2001 on water quality management and water pollution control. The results of measurements of physical and chemical parameters is the temperature range from three observation stations ranged from 26.6 to 31 ° C, ranges from 0.17 to 49.7 NTU turbidity. Total Dissolved Solids (TDS) 134-317 mg / l. Total Suspended Solids 14-96 mg / l. pH ranges from 6.69 to 7.78. Dissolved Oxygen (DO) from 0.03 to 6.22 mg / l. COD (Chemical Oxygen Demand) <4.99 to 27.75 mg / l, BOD (Biochemical Oxygen Demand) from 0.60 to 6.31 mg / l, nitrate (NO3-N) from 0.013 to 0.251 mg / l, Phosphate ( PO 4) 0.013 to 0.243 mg / l and ammonia (NH3) from 0.051 to 0.346 mg / l.